Food chemistry : the role of additives, preservatives and adulteration - Sen, Mousumi (Wiley ; Scrivener Publishing, 2022)
Food Chemistry: The Role of Additives, Preservatives and Adulteration is designed to present basic information on the composition of foods and the chemical and physical changes that their characteristics undergo during processing, storage, and handling. Details concerning recent developments and insights into the future of food chemical risk analysis are presented, along with topics such as food chemistry, the role of additives, preservatives, and food adulteration, food safety objectives, risk assessment, quality assurance, and control. Moreover, good manufacturing practices, food processing systems, design and control, and rapid methods of analysis and detection are covered, as well as sensor technology, environmental control, and safety. The book also presents detailed information about the chemistry of each major class of food additive and their multiple functionalities. In addition, numerous recent findings are covered, along with an explanation of how their quality is ascertained and consumer safety ensured.